2(m^2n+mn^2)-3(m^2n)-2mn^2-1,其中m=-2,n=2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 18:04:55
2(m^2n+mn^2)-3(m^2n)-2mn^2-1,其中m=-2,n=22(m^2n+mn^2)-3(m^2n)-2mn^2-1,其中m=-2,n=22(m^2n+mn^2)-3(m^2n)-2
2(m^2n+mn^2)-3(m^2n)-2mn^2-1,其中m=-2,n=2
2(m^2n+mn^2)-3(m^2n)-2mn^2-1,其中m=-2,n=2
2(m^2n+mn^2)-3(m^2n)-2mn^2-1,其中m=-2,n=2
先化简再求值:2(m²n+mn²)-3m²n-2mn²-1,其中m=-2,n=2
2(m²n+mn²)-3m²n-2mn²-1=-m²n-1=-(-2)²×2-1=-8-1=-9
1/M+1/N=5 (3M+MN+2N) / (M-MN=3N)
(5mn-2m+3n)+(-7m-7mn)
(5mn-2m+3n)+(-7m-7mn)
mn(m-n)-m(n-m)²2m(m-n)(2n-m)求过程
m^3n-2m^2n^2+mn^3
m²-3mn+2n²+m-n因式分解
因式分解:8mn(n-m)+2(n-m)^3
因式分解:8mn(n-m)+2(n-m)^3,
若(m+n)^2-mn(m+n)=(m+n)·M,则M是() A.m^2+n^2 B.m^2-mn+n^2 C.m^2-3mn+n^2 D.m^2+mn+n^2
(m-n)(m^5+m^4n+m^3n^2+m²n^3+mn^4+n^5)
(m^2-n^2/mn)^2÷(m+n)^2*(m/m-n)^3 化简
急2[mn+(-3m)]-3(2n-mn),m+n=2 mn=-3
3(m^2n+mn)-4(mn-2m^2n)+mn.要有过程
因式分解: m(m-2n)+n(2mn-m^2)
已知m-n=4,m、n互为倒数求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4m+mn)的值
mn(m-n)-m(n-m)2 2是平方
计算m/(m+n)+(mn)/(n^2 -m^2)
分解因式mn(m-n)-m(n-m)^2